Effect of Nitrogen Application on the Sensitivity of Desert Shrub Community Productivity to Precipitation in Central Asia - Zang, Yong-Xin; Xu, Wen-Xuan; Wu, Ke; Yang, Wei-Kang (Frontiers in Plant Science, 2022)
Precipitation variability and nitrogen (N) deposition caused by anthropogenic activities could profoundly impact ecosystem productivity and carbon cycling. In desert ecosystems, vegetation is sensitive to changes in precipitation and N deposition. However, the impacts of large changes in precipitation, especially with a concurrent increase in N content, on plant community remain unclear. In this study, we carried out experiments to monitor the impacts of five precipitation levels and two N levels on the plant community function and composition from the Junggar desert in Central Asia during the period 2018–2019. Our results showed that: (1) Aboveground net primary production (ANPP) significantly increased with increasing precipitation, and it followed a positive linear model; (2) N application led to an increase in the sensitivity of ANPP to increased precipitation but caused the sensitivity of ANPP to decrease with decreasing precipitation; (3) Changes in N content and precipitation, and their impacts on ANPP were mainly driven by community density. These results suggest that multiple constraints should be considered when assessing the sensitivity of terrestrial ecosystems to climate change.